(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Patient psychology before and after surgery should be concerned because it closely affects the treatment process and the patient’s ability to recover after surgery. Objectives: Determining the stress status of patients before and after surgery at Vinmec Times City International General Hospital in 2022 and some related factors. Methods: Cross-sectional survey, quantitative research. Results: The study collected information from 400 patients before and after surgery at Vinmec Times City International General Hospital through a questionnaire. The study results showed that the rate of patients feeling stressed before surgery was 1,8%, of which 94,5% of patients with everyday stress, 3,8% mild stress, 1,0% moderate stress, 0,3% severe stress and 0,5% very severe stress. After surgery, none of the patients were stressed. Three factors related to patient’s stress include economic dependence, time of surgery and patient’s knowledge about surgery (p<0.01).